THE BASIC EMOTIONS OF THE MAIN CHARACTER IN THE NOVEL “قلب الليل” BY NAGUIB MAHFOUZ: DAVID KRECH'S PERSPECTIVE - Al - Fara, Zulfi; Surur, Misbahus (Al-Uslub: Journal of Arabic Linguistic and Literature, 2025)
The novel “قلب الليل” tells the dramatic story of a man named Ja'far. Ja'far was once at the peak of happiness before he fell into a valley of suffering. He became impoverished, his family life fell apart, and he became involved in a politically motivated murder case. The strong emotional pressures from his past led Ja'far to face difficult situations in his life. Ja'far displays a range of emotions when confronted with these challenging situations. Therefore, this study aims to uncover the basic emotions of the main character in the novel “قلب الليل”, Ja'far, from the perspective of David Krech. This research employs David Krech's literary psychology approach to explore characters' emotions in literary works. This is a qualitative-descriptive study. The primary data source is the novel “قلب الليل” by Naguib Mahfouz. Data collection techniques include reading and note-taking. Data analysis follows the Miles and Huberman model, involving data reduction, data presentation, and conclusion drawing. The study finds that the basic emotions of the main character in the novel “قلب الليل” include: two types of anger, two types of sadness, one type of joy, and one type of fear.